2020
DOI: 10.1186/s13104-020-04996-5
|View full text |Cite
|
Sign up to set email alerts
|

MDC1 depletion promotes cisplatin induced cell death in cervical cancer cells

Abstract: Objective: Cisplatin, the most common chemotherapeutic drug for the treatment of advanced stage cervical cancers has limitations in terms of drugs resistance observed in patients partly due to functional DNA damage repair (DDR) processes in the cell. Mediator of DNA damage checkpoint 1 (MDC1) is an important protein in the Ataxia telangiectasia mutated (ATM) mediated double stranded DNA break (DSB) repair pathway. In this regard, we investigated the effect of MDC1 change in expression on the cisplatin sensitiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The sophoridine is a plant derived-natural compound that enhances sensitivity of lung cancer cells into cisplatin via induction of p53 and Hippo signaling pathways(Zhu et al, 2020). The mediator of DNA damage checkpoint 1 (MDC1) is a genetic factor that its down-regulation induces apoptosis in cervical cancer cells(Singh, Bhakuni, Chhabria, & Kirubakaran, 2020). It is worth mentioning that CT can target molecular pathways to increase cisplatin sensitivity.…”
mentioning
confidence: 99%
“…The sophoridine is a plant derived-natural compound that enhances sensitivity of lung cancer cells into cisplatin via induction of p53 and Hippo signaling pathways(Zhu et al, 2020). The mediator of DNA damage checkpoint 1 (MDC1) is a genetic factor that its down-regulation induces apoptosis in cervical cancer cells(Singh, Bhakuni, Chhabria, & Kirubakaran, 2020). It is worth mentioning that CT can target molecular pathways to increase cisplatin sensitivity.…”
mentioning
confidence: 99%
“…Next, we turned our attention to explore the activity of splice modulation on cell lines displaying sensitivity or resistance to cisplatin, as the latter is an issue in the treatment of solid tumors including ovarian [ 38 ], cervical cancer [ 39 ], gastric adenocarcinoma [ 40 ], prostate cancer [ 41 ], colorectal [ 42 ], and head and neck squamous cell carcinoma [ 43 ]. Here, we used two human ovarian cancer cell lines, one consisting of a cisplatin-sensitive parental line, OV2008, and the other stably cisplatin-resistant subline, OV2008/C13 derived by in vitro selection with cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the 33 genes in the GSE142699 dataset identified as targets of miR-199a-5p have been reported to be associated with cancer and AML. For example, the MDC1 gene, which was determined as the hub gene among these genes, was found to be closely related to many cancers (27,28). In the study by Ruff et al, it was suggested that MDC1 may be an important biomarker in carcinogenesis (29).…”
Section: Discussionmentioning
confidence: 99%